Extraction of essential oil from cinnamon (cinnamomun zeylanicum) - Ahmad Mudzaqqir Mohd Yusof (2013)
Cinnamomun Zeylanicum is one of the herbs and spices plants that come from cinnamon family which contain high quality of essential oil. From this study, the essential oil from plant Cinnamomun Zeylanicum is extracted by using two methods which is steam distillation and soxhlex extraction. Steam distillation produce high quality essential oil when separate using separatory funnel. Soxhlet extraction produces essential oil in form of crude when using rotary evaporator to purify the extract product. Cinnamon essential oil contain high cinnamaldehyde content which the main component in cinnamon. The percentage of cinnamaldehyde in essential oil from steam distillation is about 90% and from soxhlet extraction is 62 - 73%. Cinnamon essential oil has high antimicrobial properties which form clear zone when test with gram positive bacteria Bacillus subtilis s.p and a gram negative bacterium is Escherichia coil. It also show antimicrobial properties with two unknown bacteria which has unknown characteristic. Cinnamaldehyde contain high antibiotic qualities since cinnamaldehyde is the main compound in cinnamonmun zeylanicum.